Update on hirsutism - Al Robaee, Ahmad A. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2008)
Hirsutism is an important medical problem affecting about 8% of women. Despitean extensive amount of published work, some aspects of hirsutism are still controversial or understudied. This paper reviews the current data that have been published in recent years on this subject.
Keywords: Diagnosis; diagnostika; etiologija; Etiology; Hirsutism; hirsutizem; Hirzutizem; Therapy; zdravljenje